Desain Panduan Audit Tata Kelola Sistem Informasi Boost The Order (SIBORDER) di PT Telekomunikasi Indonesia Menggunakan COBIT 2019 - Kezia Nadia Putri Martinus; Evi Maria; Hanna Prillysca Chernovita (Universitas Mohammad Husni Thamrin, 2021)
PT Telekomunikasi Indonesia Tbk (Telkom) is engaged in information and communication technology and network services. Information technology (IT) plays an important role in PT Telkom's business processes, so it needs to be managed using the Control Objectives for Business and Related Technology (COBIT) framework. COBIT 2019 accommodates new IT trends in business, so that it can serve as a guide for auditors, users and management to bridge the gap between risk, control, and technical problems at PT Telkom, especially in the management of the Boost The Order (SIBORDER) Information System. IT governance audit is a control mechanism for SIBORDER management. Therefore, before conducting the audit, the auditor needs to make an audit plan to make it easier when allocating resources so that the audit is carried out effectively and efficiently. This research aims to design a SIBORDER governance audit guide using the COBIT 2019 framework. The design begins first, by identifying stakeholder needs, enterprise goals and weighting design factors. The results of stakeholder needs, namely optimizing risk and resources, while enterprise goals, namely EG01, EG05, EG06 and EG13, and the results of domain identification as focus areas, namely BAI 10, DSS 03, DSS 04 and DSS 05. Second, determination of information sources based on the RACI Chart. Third, the creation of an audit worksheet that contains a list of questions for the assessment of the selected domain and the schedule of audit implementation.